2008
DOI: 10.1143/jpsj.77.023712
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Magnetic Structure and Ferroelectricity of LiVCuO4

Abstract: Neutron scattering studies and measurements of the dielectric susceptibility ε and ferroelectric polarization P have been carried out in various magnetic fields H for single-crystal samples of the multiferroic system LiVCuO 4 with quasi one-dimensional spin 1/2 Cu 2+ chains formed of edge-sharing CuO 4 square planes, and the relationship between the magnetic structure and ferroelectricity has been studied. The ferroelectric polarization is significantly suppressed by the magnetic field H above 2 T applied alon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
66
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 20 publications
6
66
1
Order By: Relevance
“…In particular, there have been intensive experimental studies of LiCuVO 4 , exploring an unusual phase transition in magnetic field from a spiral-ordered phase to a modulated-collinear-ordered phase 12,13 and a multiferroic behavior. 14,15,16 From a theoretical point of view, the J 1 -J 2 spin chain (1) is of special interest as it is the simplest of the frustrated quantum spin models and provides a good testing ground to look for exotic quantum phases induced by frustration. The theoretical studies over the past several decades have mostly considered the case where both couplings are antiferromagnetic, J 1 > 0 and J 2 > 0.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there have been intensive experimental studies of LiCuVO 4 , exploring an unusual phase transition in magnetic field from a spiral-ordered phase to a modulated-collinear-ordered phase 12,13 and a multiferroic behavior. 14,15,16 From a theoretical point of view, the J 1 -J 2 spin chain (1) is of special interest as it is the simplest of the frustrated quantum spin models and provides a good testing ground to look for exotic quantum phases induced by frustration. The theoretical studies over the past several decades have mostly considered the case where both couplings are antiferromagnetic, J 1 > 0 and J 2 > 0.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Due to the loss of inversion symmetry associated with the spin spiral order, LiCuVO 4 becomes ferroelectric (FE) below T N . [5][6][7] Density functional theory (DFT) calculations showed 8 that this FE polarization arises from the spin-orbit coupling interactions that occur in the absence of inversion symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 However, the observation of P c, assigned to the bc-spiral spin phase, 18 was not reproduced by another group. 19 Since both compounds frequently contains Li-Cu intersubstitution due to their close ionic radii, Moskvin et al have claimed that the observed FE and ME natures stem purely from exchange striction and crystallographic defects, not from the spin-orbit interaction (or the IDM scheme). [20][21][22] Furthermore, some recent theoretical study predicted that quantum fluctuation may largely reduce the effective magnitude of P induced via the spin-orbit interaction.…”
Section: Introductionmentioning
confidence: 99%